Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.04.01.019463
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights into The Codon Usage Bias of 13 Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Isolates from Different Geo-locations

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of Coronavirus disease 2019 which is an infectious disease that spread throughout the world and was declared as a pandemic by the World Health Organization (WHO). In the present study, we analyzed genome-wide codon usage patterns in 13 SARS-CoV-2 isolates from different geo-locations (countries) by utilizing different CUB measurements. Nucleotide and di-nucleotide compositions displayed bias toward A/U content in all codon pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
3
2
0
Order By: Relevance
“…Thus, most codons of SARS-CoV-2 Wuhan-Hu-1 tended to be U ending. Moreover, the mean GC and AU compositions (Supplementary Figure 1B) were 37.9% and 62.1% (SARS-CoV-2 Wuhan-Hu-1), 41.0% and 59.0% (SARS-CoV Tor2), 40.8% and 59.2% (SARS-CoV Urbani), 41.5% and 58.5% (MERS-CoV HCoV-EMC), 36.8% and 63.2% (HCoV-OC43), 32.0% and 68.0% (HCoV-HKU1), 38.0% and 62.0% (HCoV-229E), 34.4% and 65.6% (HCoV-NL63), respectively indicating that SARS-CoV-2 Wuhan-Hu-1 as well as other human coronaviruses in this study were all AU rich, which was consistent with recent reports [11][12][13][14][15].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, most codons of SARS-CoV-2 Wuhan-Hu-1 tended to be U ending. Moreover, the mean GC and AU compositions (Supplementary Figure 1B) were 37.9% and 62.1% (SARS-CoV-2 Wuhan-Hu-1), 41.0% and 59.0% (SARS-CoV Tor2), 40.8% and 59.2% (SARS-CoV Urbani), 41.5% and 58.5% (MERS-CoV HCoV-EMC), 36.8% and 63.2% (HCoV-OC43), 32.0% and 68.0% (HCoV-HKU1), 38.0% and 62.0% (HCoV-229E), 34.4% and 65.6% (HCoV-NL63), respectively indicating that SARS-CoV-2 Wuhan-Hu-1 as well as other human coronaviruses in this study were all AU rich, which was consistent with recent reports [11][12][13][14][15].…”
Section: Resultssupporting
confidence: 92%
“…Additionally, the overall codon usage pattern of SARS-CoV-2 was generally similar to that of its phylogenetic relatives among non-human coronaviruses such as RaTG13. Our ndings are consistent with the recent observations [11][12][13][14][15] and provide new insights into the characteristics of codon usage pattern in coronaviruses. These results also have important implications for future work.…”
Section: Nucleotide Composition Analysis (Supplementarysupporting
confidence: 92%
“…Similar approaches have been employed in the development of live attenuated vaccines against poliovirus ( Coleman et al, 2009 ), human respiratory syncytial virus ( Le Nouën et al, 2014 ), influenza virus ( Mueller et al, 2011 ), and dengue virus ( Shen et al, 2015 ). The present study results are similar to that of the previous studies performed on SARS-CoV-2 structural genes, validating our findings ( Dilucca et al, 2020 ; Khodary & Anwar, 2020 ; Kandeel et al, 2020 ; Gu et al, 2020 ; Tort, Castells & Cristina, 2020 ; Nyayanit et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…The CAI values can be used to measure the extent of adaptability of the virus inside the host, its value ranges from 0 to 1. The higher value reveals higher gene expression and better adaptability in the host ( Khodary & Anwar, 2020 ). When comparing the CAI values of human isolated SARS-CoV-2 VOC with the closely related bat-CoVs and pangolin-CoVs by taking human codon usage as a reference, it was revealed similar pattern of adaptation to the human cellular system of SARS-CoV-2 and the closely related pangolin-CoV (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper by Tort et al suggested mutational pressure to be the major factor responsible for shaping the codon usage pattern (CUP) in the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [16]. In another study by Anwar et al, natural selection and other factors were considered to shape the CUP of the SARS-CoV-2 [17]. A study by Dulicca et al demonstrated the influence of both mutational and selectional pressures in shaping the CUP of the SARS-CoV-2 genes [18].…”
Section: Introductionmentioning
confidence: 99%